Need to Know? On Information Systems in Firms - Suzanne Bijkerk; Josse Delfgaauw; Vladimir A. Karamychev; Otto H. Swank (Tinbergen Institute, 2018)
In the context of firm decision-making, several motives for acquiring and conveying information exist. Information serves to make better decisions, to persuade, and to impress. In this paper, we study how these motives shape incentives to acquire and communicate information. We employ a cheap-talk model with information acquisition and communication by a firm's executive. The executive wants to accurately inform an internal decision-maker regarding the value of an opportunity, but has an incentive to overstate this value to persuade or impress external parties. We show that information acquisition and communication interact. The executive's impression and persuasion motives yield limited distortions in communication, if any. Instead, they reduce information acquisition. Furthermore, we find that for firms, transparent communication is a necessary evil. Transparency allows for influential communication to external parties, but constrains internal communication. Theoretically, we contribute by showing that the forward induction refinement excludes babbling as an equilibrium outcome if non-babbling equilibria exist.
Keywords: D21; D83; 330; Information system; Information acquisition; Cheap-talk; Transparency; Firm behavior